2022
DOI: 10.31635/ccschem.021.202101067
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Microphase Behaviors of Chiral Block Copolymers under Kinetic and Thermodynamic Control

Abstract: The chiral superstructures in confined space are subtly affected by the complex interplays among various noncovalent interactions, details of which are still inadequately understood. Here, we report the 3D confined assembly of chiral block copolymer of polystyrene-block-poly(D-lactide) and its enantiomer in emulsion droplets, and demonstrate unprecedented successive microphase transformations from single helices to double helices with inverted helicity, and then to twisted cylinders in the constructed colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Furthermore, it evidenced the homochiral transfer from the PLLA/PDLA configuration to the PLLA/PDLA internal helixes*. [183] Not only did these contributions paved a pathway to a controlled confined assembly of BCPs*, it also inspired further investigations on how confinement would impact the morphological chirality of BCP* assemblies.…”
Section: Self-assembly Of Bcps* Under Confinementmentioning
confidence: 93%
“…Furthermore, it evidenced the homochiral transfer from the PLLA/PDLA configuration to the PLLA/PDLA internal helixes*. [183] Not only did these contributions paved a pathway to a controlled confined assembly of BCPs*, it also inspired further investigations on how confinement would impact the morphological chirality of BCP* assemblies.…”
Section: Self-assembly Of Bcps* Under Confinementmentioning
confidence: 93%
“…[ 12 ] In the past decade, many studies have been reported on controlling the morphologies of BCP colloidal particles by varying the volume fraction, degree of confinement, solvent selectivity, evaporation dynamics, and interfacial interaction. [ 4,15–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…[12] In the past decade, many studies have been reported on controlling the morphologies of BCP colloidal particles by varying the volume fraction, degree of confinement, solvent selectivity, evaporation dynamics, and interfacial interaction. [4,[15][16][17][18][19][20][21][22][23][24][25] In emulsion droplets, interfacial selectivity (relative affinity of each block with the continuous phase) determines the segment orientation of BCP and thereby the morphology of the assemblies. [2,26,27] The interfacial selectivity can be adjusted by varying the properties of the surfactants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, helical polymers are widely used in many fields such as ferroelectric liquid crystals (LCs), enantiomer separation, asymmetric catalysis and so on 5–10 . Therefore, chemists have made many efforts to design and synthesize plenty of synthetic helical polymers, oligomers and helical assemblies 11–19 …”
Section: Introductionmentioning
confidence: 99%